Implementing cyber security incident response playbook in a Philippine power-grid company - Domingo, Keinaz N. (Animo Repository, 2022)
The incident response security playbook's objective is to offer all employees an organization with a clear awareness of their duties toward cybersecurity standards and recognized practices before, during, and after a security incident. Every organization has preparations in place for various incidents that could have an impact on the business’ resilience if they are not prepared. Mori (2021) conducted a Cyber Security Breaches Survey which revealed that 40% of firms and 25% of charities reported cyber security breaches or assaults. The COVID-19 outbreak has resulted in substantial modifications in working methods, including difficulty in power grid cybersecurity. With this, the incident response should focus on the possible issues that the company could experience and give awareness to the organization. The paper presents the step by step playbook that very organization has preparations in place for various incidents that could have an impact on the business’ resilience if they are not prepared.